Diverse forms of pin-II family proteinase inhibitors from capsicum annuum adversely affect the growth and development of helicoverpa armigera - Tamhane, Vaijayantl A.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Gene, 2007)
Novel forms of Pin-II type proteinase inhibitor (PIs) cDNAs (CanPIs) having three or four inhibitory repeat domains (IRD) were isolated from the developing green fruits of Capsicum annuum. Deduced amino acid (aa) sequences of the CanPIs showed up to 15% sequence divergence among each other or reported inhibitors (CanPI-1 AF039398, CanPI-2 AF221097). Amino acid sequence analysis of these CanPIs revealed that three IRD Pls have trypsin inhibitory sites, while four IRD CanPIs have both trypsin and chymotrypsin inhibitory sites. Four CanPIs, two having three IRD (CanPI-3 AY986465 and CanPI-5 DQ005912) and two having four IRD (CanPI-7 DQ005913 and CanPI-9 DQ005915), were cloned in Pichia pastoris to express recombinant CanPIs. Recombinant CanPIs inhibited 90% of bovine trypsin (TI), while chymotrypsin inhibition (0) varied with the number of chymotrypsin inhibitory sites in the CanPIs. Recombinant inhibitors inhibited over 70% of the gut proteinase activity of Helicoverpa armigera. H. armigera larvae fed on recombinant CanPIs individually incorporated into artificial diet, showed 35% mortality; in addition, weight gain in H. armigera larvae and pupae was severely reduced compared to controls. Of the four CanPIs, CanPI-7, which has two sites for TI and CI, was the only one to have a consistently antagonistic effect on H. armigera growth and development. We conclude that among the four recombinant Pls tested, CanPIs containing diverse IRDs are best suited for developing insect-resistant transgenic plants. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: insect resistance; IP repeats; PI-insect interaction; Pichia pastoris; potato type 2 inhibitors (Pot-II); Solanaceae